A kind of viscoelastic anticorrosion tape and preparation method thereof
By adjusting the distribution ratio and layer thickness of the polyolefin layer and sticky bomb body layer, combined with the combination of high -density polyethylene, low -density polyethylene and conductive carbon black, the existing sticky bomb body anticorrosive tape adhesive and construction The problem of complexity realizes efficient bonding performance and good chemical resistance.
Patent Information
- Application Number
- CN202310346640.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-04-03
AI Technical Summary
The existing viscoelastic anticorrosion tape has high complexity during construction, insufficient adhesion between primer and anticorrosion tape, which is prone to aging failure, and the blending system of rubber and acrylate is poor, resulting in a reduced bonding performance. .
By adjusting the distribution ratio and layer thickness of the polyolefin layer and the sticky bomb body layer, the combination of high -density polyethylene, low -density polyethylene and conductive carbon black is used to improve the resistance of anticidering and stretching; The combination of polyet cluttotyne, halide butadyl rubber and fillers increases bonding performance, and further improves the bonding performance and peeling strength by adding acrylic rubber and adhesives.
The excellent adhesion and mechanical properties of adhesive corrosion tape are realized. At the same time, it has good chemical resistance and reduces construction complexity.
Smart Images

Figure BDA0004160029650000061 
Figure BDA0004160029650000071
Abstract
Description
Technical Field
[0001] The present invention relates to the field of viscoelastic technology, in particular to the field of IPC C09J7, and more specifically to a viscoelastic anti-corrosion tape and a preparation method thereof. Background Art
[0002] Viscoelastic anti-corrosion tape is an anti-corrosion product specially designed for buried pipelines and other special-shaped equipment that need to be anti-corroded, such as flanges, valves, pumps, etc. It is a new type of high-performance viscoelastic polyolefin material that has the dual characteristics of solid adhesive materials and liquid adhesive materials. Under normal conditions, the viscoelastic properties of viscoelastic anti-corrosion tape can be maintained for more than decades, with excellent adhesion, waterproof sealing, and easy operation. Polyethylene anti-corrosion tape is a commonly used anti-corrosion tape for underground pipelines, but currently it is usually made of primer + anti-corrosion tape + protective tape, which increases the complexity of construction. At the same time, the adhesion between the primer and the anti-corrosion tape is not high enough, and it is easy to age and fail.
[0003] CN 106281092 A discloses a polyethylene anticorrosive tape for underground pipelines, wherein the adhesive layer is made of the following components: 30-45 parts of butyl rubber, 10-15 parts of nitrile rubber, 15-25 parts of polyurethane acrylate, 25-35 parts of epoxy resin, 10-15 parts of 1,6-hexanediol diacrylate, 5-10 parts of FRP waste, 5-10 parts of pentaerythritol stearate, 5-10 parts of dibutyl phthalate, 10-15 parts of carbon black, 5-10 parts of graphene, 1-5 parts of expanded perlite, 1-5 parts of hydroxyethyl cellulose, 0.5-1 parts of tetramethylthiuram disulfide, 0.5-3 parts of polyacrylamide, and 1-3 parts of antioxidant. In the invention, the blending system of rubber and acrylate is prone to reduce the bonding performance to a certain extent due to compatibility. Summary of the invention
[0004] In order to overcome the shortcomings of the background technology, the present invention provides a viscoelastic anti-corrosion tape and a preparation method thereof. By adjusting the ratio between components and the thickness between layers, the prepared viscoelastic anti-corrosion tape achieves excellent bonding properties and mechanical properties, and also has good chemical resistance.
[0005] To achieve the purpose of the present invention, the first aspect of the present invention provides a viscoelastic anti-corrosion tape, comprising a polyolefin layer and a viscoelastic layer; the polyolefin layer comprises, by weight, 60-80 parts of high-density polyethylene, 20-40 parts of low-density polyethylene, and 1-5 parts of conductive carbon black; the viscoelastic layer comprises, by weight, 40-60 parts of polyisobutylene, 10-30 parts of halogenated butyl rubber, 10-25 parts of filler, 3-8 parts of acrylate rubber, 3-8 parts of tackifier, and 2-5 parts of antioxidant.
[0006] The thickness of the polyolefin layer is 0.4-0.6 mm.
[0007] Preferably, the polyolefin layer has a thickness of 0.45 mm.
[0008] The thickness ratio of the polyolefin layer to the viscoelastic layer is 1:(2.5-4).
[0009] Preferably, the thickness ratio of the polyolefin layer to the viscoelastic layer is 1:3.
[0010] The high-density polyethylene melt flow index (190° C., 2.16 Kg) is 0.5-1.2 g / 10 min.
[0011] Preferably, the high-density polyethylene has a melt flow index of 1.1 g / 10 min and is purchased from Sinopec with a grade of 3300F.
[0012] The low-density polyethylene has a melt flow index of 0.1-0.5 g / 10 min.
[0013] Preferably, the low-density polyethylene has a melt flow index (190°C, 2.16Kg) of 0.33 g / 10 min and is purchased from Yanshan Petrochemical with the brand name LD165.
[0014] The polyethylene anticorrosive tape substrate has the advantages of acid resistance, alkali resistance, oil resistance, and corrosion resistance, but the polyethylene substrate is very easy to generate static electricity. The accumulation of static electricity may lead to static spark discharge. The applicant has found that the weight ratio of high-density polyethylene, low-density polyethylene, and conductive carbon black is 75:25:2, which can not only improve the antistatic performance of the polyolefin layer, but also improve the tensile properties of the tape. It is speculated that the conductive carbon black contacts each other in the polymer matrix to form a certain number of aggregates with irregular fibrous structures, with a large void volume, which increases the contact points of the particles in the composite system, reduces the distance between the polymer chain segments, and increases the force between the chain segments, thereby improving the tensile properties of the tape. Further research has found that the specific surface area of the conductive carbon black is 300-700m 2 / g, can improve the processing performance of the polyolefin layer. The larger the specific surface area, the worse the dispersion and fluidity of carbon black, which is not conducive to molding processing. If the specific surface area is too small, the residual stress between the polyolefin chain segments will be too large, which will easily lead to reduced mechanical properties.
[0015] The weight ratio of the high-density polyethylene, the low-density polyethylene and the conductive carbon black is 1:(0.3-0.7):(0.01-0.03).
[0016] Preferably, the weight ratio of the high-density polyethylene, low-density polyethylene and conductive carbon black is 75:25:2.
[0017] The conductive carbon black has a specific surface area of 300-700 m 2 / g.
[0018] Preferably, the conductive carbon black has a specific surface area of 400 m 2 / g, purchased from Hebei Moyu Chemical Co., Ltd., model: M80.
[0019] The polyisobutylene comprises high molecular weight polyisobutylene and low molecular weight polyisobutylene, and the weight ratio of the high molecular weight polyisobutylene to the low molecular weight polyisobutylene is (2-5):1.
[0020] Preferably, the polyisobutylene comprises high molecular weight polyisobutylene and low molecular weight polyisobutylene, and the weight ratio of the high molecular weight polyisobutylene to the low molecular weight polyisobutylene is (3-5):1.
[0021] Further preferably, the polyisobutylene comprises high molecular weight polyisobutylene and low molecular weight polyisobutylene, and the weight ratio of the high molecular weight polyisobutylene to the low molecular weight polyisobutylene is 3.5:1.
[0022] The molecular weight of the high molecular weight polyisobutylene is 180,000-250,000, and the molecular weight of the low molecular weight polyisobutylene is 2,000-5,000.
[0023] Preferably, the high molecular weight polyisobutylene has a molecular weight of 200,000 and is purchased from BASF with the brand name Oppanol B30, and the low molecular weight polyisobutylene has a molecular weight of 2400 and is purchased from Hengtai Petrochemical with the brand name HT-24.
[0024] The viscosity (30° C.) of the acrylic rubber is 10,000-50,000 cps.
[0025] Preferably, the viscosity (30° C.) of the acrylic rubber is 20,000-50,000 cps.
[0026] Preferably, the acrylic rubber comprises epoxy-terminated liquid acrylic rubber.
[0027] More preferably, the epoxy-terminated liquid acrylate rubber has a viscosity (30° C.) of 30,000 cps and is purchased from Yuyao Huihong Plastic Factory, model: ER-120.
[0028] The molecular weight of the halogenated butyl rubber is 80,000-200,000.
[0029] Preferably, the halogenated butyl rubber has a molecular weight of 100,000 and is purchased from Dongguan Mingyuan Plastic Co., Ltd.
[0030] The mesh number of the filler is 200-2000 mesh.
[0031] Preferably, the mesh size of the filler is 800-1250 meshes.
[0032] The filler includes one of talcum powder, precipitated barium sulfate, silicon powder, calcium carbonate and silicon dioxide.
[0033] Preferably, the filler comprises talc and silicon dioxide, and the weight ratio of the talc to silicon dioxide is 1:(0.3-1).
[0034] Further preferably, the filler includes talcum powder and silicon dioxide, and the weight ratio of the talcum powder to the silicon dioxide is 1:0.5.
[0035] Preferably, the talc powder has a mesh size of 1000 and is purchased from Guangxi Longguang Talc Development Co., Ltd., and the silica has a mesh size of 1000 and is purchased from Tianjin Kedierhan Technology Co., Ltd.
[0036] The weight ratio of the polyisobutylene, the halogenated butyl rubber and the filler is 1:(0.2-0.45):(0.1-0.35).
[0037] Preferably, the weight ratio of the polyisobutylene, the halogenated butyl rubber and the filler is 25:11:7.
[0038] The tackifier includes at least one of liquid terpene resin, rosin resin and C5 petroleum resin.
[0039] Preferably, the tackifier comprises rosin resin purchased from Jinan Shunyang Chemical Technology Co., Ltd.
[0040] Preferably, the antioxidant comprises 2,6-di-tert-butyl-4-methylphenol.
[0041] A second aspect of the present invention provides a viscoelastic anti-corrosion tape and a preparation method thereof, comprising the following steps:
[0042] S1, mixing high-density polyethylene, low-density polyethylene and conductive carbon black uniformly, adding the mixture into an extruder, and extruding the mixture at 150-180° C. to obtain a polyolefin layer;
[0043] S2, adding polyisobutylene, halogenated butyl rubber, filler, acrylic rubber, tackifier, and antioxidant in sequence, mixing them evenly through banburying, and extruding to obtain a viscoelastic layer material;
[0044] S3, heating the viscoelastic layer material to a molten state, and coating it on the polyolefin layer by an automatic coating machine to obtain.
[0045] The coating amount is 10-18g / m 2 .
[0046] Preferably, the coating amount is 14g / m 2 .
[0047] The temperature of the banburying is 110-130° C., and the time of the banburying is 25-45 min.
[0048] Preferably, the banburying temperature is 120° C., and the banburying time is 30 min.
[0049] Beneficial effects:
[0050] 1. The weight ratio of high-density polyethylene, low-density polyethylene and conductive carbon black is 75:25:2, which can not only improve the antistatic performance of the polyolefin layer, but also improve the tensile performance of the tape.
[0051] 2. The specific surface area of the conductive carbon black is 300-700m 2 / g, which can improve the antistatic properties and processing performance of the anti-corrosion tape.
[0052] 3. The weight ratio of the polyisobutylene, halogenated butyl rubber and filler is 1:(0.2-0.45):(0.1-0.35), which can improve the bonding performance of the anti-corrosion tape.
[0053] 4. By adding acrylic rubber with a viscosity of 10,000-50,000 cps, the bonding performance and peel strength of the anti-corrosion tape can be further improved.
[0054] 5. The polyisobutylene includes high molecular weight polyisobutylene and low molecular weight polyisobutylene, and the weight ratio of the high molecular weight polyisobutylene to the low molecular weight polyisobutylene is (2-5):1, which can improve the bonding performance and chemical resistance of the anti-corrosion material. DETAILED DESCRIPTION
[0055] Example 1
[0056] A viscoelastic anti-corrosion tape comprises a polyolefin layer, wherein the viscoelastic layer comprises, by weight, 75 parts of high-density polyethylene, 25 parts of low-density polyethylene, and 2 parts of conductive carbon black; and the viscoelastic layer comprises, by weight, 50 parts of polyisobutylene, 22 parts of halogenated butyl rubber, 14 parts of filler, 4 parts of acrylic rubber, 3 parts of tackifier, and 2 parts of antioxidant.
[0057] The thickness of the polyolefin layer is 0.45 mm.
[0058] The thickness ratio of the polyolefin layer to the viscoelastic layer is 1:3.
[0059] The high-density polyethylene has a melt flow index of 1.1 g / 10 min and is purchased from Sinopec with a grade of 3300F.
[0060] The low-density polyethylene has a melt flow index of 0.33 g / 10 min and is purchased from Yanshan Petrochemical Company with a grade of LD165.
[0061] The conductive carbon black has a specific surface area of 400 m 2 / g, purchased from Hebei Moyu Chemical Co., Ltd., model: M80.
[0062] The polyisobutylene comprises high molecular weight polyisobutylene and low molecular weight polyisobutylene, and the weight ratio of the high molecular weight polyisobutylene to the low molecular weight polyisobutylene is 3.5:1.
[0063] The high molecular weight polyisobutylene has a molecular weight of 200,000 and is purchased from BASF with the brand name Oppanol B30. The low molecular weight polyisobutylene has a molecular weight of 2400 and is purchased from Hengtai Petrochemical with the brand name HT-24.
[0064] The acrylic rubber is an epoxy-terminated liquid acrylic rubber.
[0065] The epoxy-terminated liquid acrylate rubber has a viscosity (30° C.) of 30,000 cps and is purchased from Yuyao Huihong Plastic Factory, model: ER-120.
[0066] The halogenated butyl rubber has a molecular weight of 100,000 and is purchased from Dongguan Mingyuan Plastic Co., Ltd.
[0067] The filler is talcum powder and silicon dioxide, and the weight ratio of the talcum powder to the silicon dioxide is 1:0.5.
[0068] The talc powder has a mesh size of 1000 and is purchased from Guangxi Longguang Talc Development Co., Ltd. The silicon dioxide has a mesh size of 1000 and is purchased from Tianjin Kedierhan Technology Co., Ltd.
[0069] The tackifier is rosin resin purchased from Jinan Shunyang Chemical Technology Co., Ltd.
[0070] The antioxidant is 2,6-di-tert-butyl-4-methylphenol.
[0071] A viscoelastic anti-corrosion tape and a preparation method thereof, comprising the following steps:
[0072] S1, mixing high-density polyethylene, low-density polyethylene and conductive carbon black uniformly, adding the mixture into an extruder, and extruding the mixture at 160° C. to obtain a polyolefin layer;
[0073] S2, adding polyisobutylene, halogenated butyl rubber, filler, acrylic rubber, tackifier, and antioxidant in sequence, mixing them evenly through banburying, and extruding to obtain a viscoelastic layer material;
[0074] S3, heating the viscoelastic layer material to 180°C to a molten state, and coating it on the polyolefin layer by an automatic coating machine to obtain.
[0075] The coating amount is 14g / m 2 .
[0076] The temperature of the banburying is 120° C., and the time of the banburying is 30 min.
[0077] Example 2
[0078] The specific implementation is the same as that of Example 1; the difference is that the polyolefin layer in Example 2 comprises 73 parts of high-density polyethylene, 23 parts of low-density polyethylene, and 2.2 parts of conductive carbon black.
[0079] Example 3
[0080] The specific implementation is the same as that of Example 1; the difference is that the viscoelastic layer in Example 3 comprises the following components: 50 parts of polyisobutylene, 24 parts of halogenated butyl rubber, 12 parts of filler, 4 parts of acrylic rubber, 3 parts of tackifier, and 2 parts of antioxidant.
[0081] Comparative Example 1
[0082] The specific implementation is the same as Example 1; the difference is that the polyolefin layer in Comparative Example 1 comprises 70 parts of high-density polyethylene, 30 parts of low-density polyethylene, and 2 parts of conductive carbon black.
[0083] Comparative Example 2
[0084] The specific implementation is the same as Example 1; the difference is that the viscoelastic layer in Comparative Example 2 comprises: 45 parts of polyisobutylene, 27 parts of halogenated butyl rubber, 15 parts of filler, 4 parts of acrylate rubber, 3 parts of tackifier, and 2 parts of antioxidant.
[0085] Comparative Example 3
[0086] The specific implementation is the same as Example 1; the difference is that the weight ratio of the high molecular weight polyisobutylene to the low molecular weight polyisobutylene in Comparative Example 3 is 2.5:1.
[0087] Performance Testing Methods
[0088] The viscoelastic anti-corrosion tapes obtained in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, and the test data are listed in Table 1.
[0089] 1) Insulation resistivity (100d) Ω·m 2 : Refer to DIN30670-91.
[0090] 2) Shear strength (MPa): ISO21809-3 Appendix L, bonding substrate: shrink tape / steel
[0091] 3) Peel strength (MPa): Refer to Appendix D of ISO21809-3, bonding temperature 23°C, bonding substrates are PE and steel respectively.
[0092] 4) Cathodic peeling (mm): refer to Appendix D of GB / T23257-2009, test temperature 23℃, test voltage -3.5V, test time 24h.
[0093] Performance test data
[0094] Table 1
[0095]
[0096]
Claims
1. A viscoelastic anti-corrosion tape, characterized in that: comprising a polyolefin layer and a viscoelastic layer; In parts by weight, the polyolefin layer comprises: 60-80 parts of high-density polyethylene, 20-40 parts of low-density polyethylene, and 1-5 parts of conductive carbon black; the viscoelastic layer comprises: 40-60 parts of polyisobutylene, 10-30 parts of halogenated butyl rubber, 10-25 parts of filler, 3-8 parts of acrylic rubber, 3-8 parts of tackifier, and 2-5 parts of antioxidant; The polyisobutylene comprises high molecular weight polyisobutylene and low molecular weight polyisobutylene, and the weight ratio of the high molecular weight polyisobutylene to the low molecular weight polyisobutylene is (3-5):1; The high molecular weight polyisobutylene has a molecular weight of 180,000-250,000, and the low molecular weight polyisobutylene has a molecular weight of 2,000-5,000; The weight ratio of high-density polyethylene, low-density polyethylene and conductive carbon black is 75:25:2; The weight ratio of the polyisobutylene, the halogenated butyl rubber and the filler is 1:(0.2-0.45):(0.1-0.35).
2. The viscoelastic anti-corrosion tape according to claim 1, characterized in that: The thickness ratio of the polyolefin layer to the viscoelastic layer is 1:(2.5-4).
3. The viscoelastic anti-corrosion tape according to claim 2, characterized in that: The viscosity of the acrylic rubber is 20000-40000 cps.
4. The viscoelastic anti-corrosion tape according to claim 3, characterized in that: The molecular weight of the halogenated butyl rubber is 80,000-200,000.
5. The viscoelastic anti-corrosion tape according to claim 4, characterized in that: The mesh number of the filler is 200-2000 mesh.
6. A method for preparing the viscoelastic anti-corrosion tape according to claim 1, characterized in that: The following steps are involved: S1, mixing high-density polyethylene, low-density polyethylene and conductive carbon black uniformly, adding the mixture into an extruder, and extruding the mixture at 150-180° C. to obtain a polyolefin layer; S2, adding polyisobutylene, halogenated butyl rubber, filler, acrylic rubber, tackifier, and antioxidant in sequence, mixing them evenly through banburying, and extruding to obtain a viscoelastic layer material; S3, heating the viscoelastic layer material to a molten state, and coating it on the polyolefin layer by an automatic coating machine to obtain.
7. The method for preparing a viscoelastic anti-corrosion tape according to claim 6, characterized in that: The coating amount is 10-18g / m 2 .
8. The method for preparing a viscoelastic anti-corrosion tape according to claim 7, characterized in that: The temperature of the banburying is 110-130° C., and the time of the banburying is 25-45 min.
Citation Information
Patent Citations
Anticorrosive polyethylene adhesive tape for underground pipeline
CN106281092A
Cold-tangled anticorrosion adhesive tape for pipeline anticorrosion
CN103602291A
Rubber-based pressure-sensitive adhesive
CN107109171A